After nasopharyngeal infection, foot-and-mouth disease virus serotype A RNA is shed in bovine milk without associated mastitis. (September 2021) - Suchowski, Marcel; Eschbaumer, Michael; Teifke, Jens P.; Ulrich, Reiner
Foot-and-mouth disease (FMD) is a highly contagious aphthoviral infection of cloven-hoofed animals, inducing vesiculopustular stomatitis, pododermatitis, and thelitis. Vesicular fluid represents a major pathway of virus excretion, but bovine milk is another important source of virus shedding. We describe here the time course of FMD virus (FMDV) excretion in the milk and characterize associated lesions in the mammary gland. Three dairy cows were infected by nasopharyngeal instillation of FMDV and monitored over 12 d. Autopsy was performed at the end of the study, and specimens were collected for histopathology, IHC, and RT-qPCR. All 3 cows developed fever, drooling, vesiculopustular stomatitis, interdigital dermatitis, and thelitis. FMDV RNA was detectable in whole milk until the end of the trial, but only transiently in saliva, nasal secretions, and blood serum. Although histology confirmed vesiculopustular lesions in the oral and epidermal specimens, the mammary glands did not have unequivocal evidence of FMDV-induced inflammation. FMDV antigen was detectable in skin and oral mucosa, but not in the mammary gland, and FMDV RNA was detectable in 9 of 29 samples of squamous epithelia but only in 1 of 12 samples of mammary gland.